ELECTORAL PARTICIPATION,KNOWLEDGE, ATTITUDE AND PRACTICES : A CASE STUDY OF UTTAR PRADESH ASSEMBLY ELECTION 2012 (INDIA) - Zutshi, Bupinder (European Scientific Journal, ESJ, 2014)
The study of voter turnout rates, its composition, characteristics, Knowledge, Attitude, Behavior, Beliefs and Practices (KABBP) is an integral part of election management by the Election Commissions throughout the World. The Office of the Chief Electoral Officer-Uttar Pradesh has taken up a Systematic Voters’ Education and Electoral Participation (SVEEP) interventions and programmebefore the Uttar Pradesh Assembly elections in 2012, to promote participation of the voter in the electoral process. The present study examines the voter turnout rates across gender groups, age groups, income groups, occupational groups and education levels in Uttar Pradesh state of India. It also attempts to assess knowledge, attitude, practices and satisfaction level of voters about various services and facilities of electoral process/election management and its consequences on voter turnout rates. The study indicates voter turnout rate of 59.48% in 2012, as compared to 46.07% in 2007 and 47.79% in General Election of 2009. The mean and median voter turnout rates recorded during 1951-2009 has been 50. I %, and 50.5% respectively,with Standard Deviation of 9.4 for the same period. However significant variations in the voter turnout rates were recorded among micro regions within same administrative constituency due to demographic, cultural, socio-economic and institutional management measures. The results point out significant impact in voter turnout rates after interventions under SVEEP were initiated by the Election Commission in 2010. The study also depicts that there is lot of gap between what the voters ‗should know‘ and what they ‗actually know‘ in important areas like registration of voter list, making of Elector Photo Identity Cards (EPIC), Polling Station location, use of Electronic Voting Machines (EVMs), do‘s & don‘ts with regard to model code of conduct. The results point out that persistent voter education with the kind of seriousness and depth, it deserves by the Election Management bodies should be given due and strong emphasis.